2020
DOI: 10.1002/imhj.21889
|View full text |Cite
|
Sign up to set email alerts
|

The role of consultative alliance in infant and early childhood mental health consultation: Child, teacher, and classroom outcomes

Abstract: Young children's social-emotional development is powerfully shaped by their early environments, which for many includes early childhood education (ECE). Infant and Early Childhood Mental Health Consultation (IECMHC) pairs teachers and infant and early childhood mental health (IECMH) consultants to promote teachers' capacity to foster positive social-emotional development in ECE. Although the outcomes of IECMHC have been well studied, little research has investigated how this model leads to changes for teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
0
16
0
3
Order By: Relevance
“…Teacher-student relationships are often mentioned as one of the core reasons for staying in the profession (O'Connor 2010). Furthermore, the professional development has also been shown to be related to improved teachers' well-being, self--efficacy, sense of autonomy, and reduction in burnout levels (Davis et al, 2021;Sandilos et al, 2020;Wolf et al, 2018). Similarly, research has shown that support provided by the school leadership, is an important defining factor for retention and commitment to the teaching profession (Beltman et al, 2018;Peixoto et al, 2018).…”
Section: Early Childhood Teachers' Professional Development Opportunitiesmentioning
confidence: 99%
“…Teacher-student relationships are often mentioned as one of the core reasons for staying in the profession (O'Connor 2010). Furthermore, the professional development has also been shown to be related to improved teachers' well-being, self--efficacy, sense of autonomy, and reduction in burnout levels (Davis et al, 2021;Sandilos et al, 2020;Wolf et al, 2018). Similarly, research has shown that support provided by the school leadership, is an important defining factor for retention and commitment to the teaching profession (Beltman et al, 2018;Peixoto et al, 2018).…”
Section: Early Childhood Teachers' Professional Development Opportunitiesmentioning
confidence: 99%
“…Recent research on an infant and early childhood mental health consultation program supports this notion of a parallel process. Specifically, a stronger consultative alliance (defined as the quality of the partnership between a consultant and teacher) was linked to greater improvements in teachers' perceptions of close relationships with children (Davis et al, 2021). A strong relationship between a consultant and teacher could similarly influence dyadic teacher-child interactions.…”
Section: Direct Links Between Relationship Quality and Dyadic Teacher-child Interactionsmentioning
confidence: 99%
“…The differences in staff educational attainment at these two levels of ECEC reflect the different value placed on education versus care, despite their interwoven nature in ECEC settings. This distinction also comes into play in different training profiles among teachers and assistants, even within the preprimary sector (Van Laere, Peeters and Vandenbroeck, 2012 [67]).…”
Section: Early Childhood Education and Care Staff Are Gaining Recogni...mentioning
confidence: 99%
“…staff-child interactions, staff motivation for achieving the centre goals, community and parental/guardian engagement), as well as on management and administrative tasks (e.g. hiring staff, managing budgets) (Daniëls, Hondeghem and Dochy, 2019 [67]; Douglass, 2018 [68]). While different dimensions of leadership are important for quality, pedagogical leadership, depending on the context and situation, can play an important role in shaping everyday classroom practices (Halpern, Szecsi and Mak, 2020[69]).…”
Section: Allocated Time To Perform Various Tasksmentioning
confidence: 99%
See 1 more Smart Citation